UI/UX Design Prototype for Enhancing User Experience using User-Centered Method - Egia Rosi Subhiyakto; Yani Parti Astuti (Universitas Negeri Semarang, 2023)
Purpose: The teaching matrix often relies on conventional methods involving explanations on a board. It makes students easily bored and relatively focused for only a short period. Integrating multimedia features such as text, colors, and sound might enhance students' comfort and engagement in the learning matrix. In this study, we discuss how to design low-fidelity and high-fidelity prototypes to enhance the comfort of the learning matrix and give a solution to manage course and communication between teachers and students.Methods: We employed the User-Centered Design method, focusing on users as the central design consideration. The User-Centered Design process involves the analysis of user needs and context, followed by requirements identification, design solutions, and solution evaluation. Results: Based on the testing results, we scored 86.25%, categorizing it as